Effects of an Inclusive Leadership Style on Team Performance: The Significance of Promoting Team Innovation Culture in Hanoi-based Software Outsourcing Firms - Thanh, Nguyen Dac; Sam, Nguyen Thi; Phương, Tran Thi Minh; Nhung, Nguyen Thi Cam; Chi, Chu Duc (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
Inclusive leadership styles have been considered as a way of useful leadership in the organization. This paper aims at testing the impact of inclusive leadership styles on Agile team’s perfomance in IT firms, besides this paper also focus on the role of mediating of innovation culture in this relationship. This research introduces empirical evidences from 876 samples in project team via fit model estimation, scale measurement and SEM PLS estimation. The results has reveal that innovation culture plays an important mediating roles in the relationship between inclusive leadership styles and team’s performance, besides innovation cultures has also influenced positively on personal innovativeness toward improving team’s performance. Based on current results it’s necessary to begin creating innovation cuulture framework including the spirit of personel, database process and technological infrastructure in order to assess innovation approach of enterprise. Finally, several managerial implementation will be discussed as enhancing vitural collaboration application, building a vitural team, digital leadership orientation as a mean of promoting and enhancing innovation culture in IT company toward digital transformation and response effectively current changes